Additional feet-on-the-street deployment method for indexed crime prevention initiative - Mohammed Ariff Abdullah; Siti Norul Huda Sheikh Abdullah; Md Jan Nordin (Penerbit Universiti Kebangsaan Malaysia, 2018)
Under the National Key Result Area (NKRA) Safe City Program’s (SCP) Safe City Monitoring System (SCMS) initiative, the Royal Malaysian Police (RMP) manages the deployment of feet-on-the-street via the indexed crime hotspots. Working on an approach known as the Repeat Location Finder (RLF), the RMP determines the displacement of indexed crime on the hotspots and may deploy feet-on-the-streets at the identified displacement areas as crime prevention measures. This paper introduces another deployment capability by shifting the focus from the hotspots to the identified serial suspects. Displacement models work on the concentration of crime incidents and the propensity location where the concentration might shift to the surrounding immediate hotspots. This additional method on the other hand, works on the identified suspects and identifies the next location where the suspects might surface, which may take place beyond the distance and boundaries of the hotspots. The objective of this paper is to identify the spatial features that positively contribute towards this new method. The solutions to the objective have been tested on a dataset made available by the RMP comprising 74 serial criminal suspects around the areas of Selangor, Kuala Lumpur and Putrajaya, spanning from Jan 1st to Dec 31st 2013. The identification capability moves as high as 92.86%. The RMP has been presented with the results of this paper and it was concluded that this method may be applicable as another capability in managing the deployment of feet-on-the-street resources.